Reuters Institute Digital News Report 2015: Supplementary report - Fletcher, R; Radcliffe, D; Levy, DAL; Nielsen, RK; Newman, N (Reuters Institute for the Study of Journalism, 2015)
The Reuters Institute Supplementary Digital News Report presents the results of an online survey on all aspects of digital new consumption in six European countries: Austria, Czech Republic, Netherlands, Poland, Portugal, and Turkey. The report forms part of the largest ongoing survey of digital news consumption in the world, surveying a total of over 30,000 respondents in 18 countries in 2015. The results shine a light on some of the most important recent trends in news consumption, such as the move to mobile news access, the emergence of new digital-born news sources, generational differences in consumption patterns, and the rise social media, news aggregators, and other digital intermediaries.